STUDI PERENCANAAN LAMPU LALU LINTAS DIPERSIMPANGAN JL. TANJUNG RAYA 2 – JL. PANGLIMA AIM DAN DIKOORDINASIKAN TERHADAP PERSIMPANGAN JL. SULTAN HAMID II – JL. TANJUNG RAYA1 – JL. PERINTIS KEMERDEKAAN – JL. TANJUNG RAYA 2 DI KOTA PONTIANAK - Kurrahman, Taupik; Widodo, Slamet; ., Akhmadali (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
No existence Traffic Management At junction Panglima Aim street - Tanjung Raya 2 street because Conflict Traffic Flows The Distributed From the intersection of Sultan Hamid street - Tanjung Raya 1 street –Perintis Kemerdekaan street - Tanjung Raya 2 street Just Located 185m, Disadvantaged Drain The Large flows From Both Junctions.For Conflict Resolution Traffic Flow At the junction of Ali Anyang street By Limiting Number of Vehicles That Go To Roads Between intersections Of Two-Way Intersection Namely Amounting 1250 Smp / Clock With Average Time 25 Seconds, Where Condition Flow Such is a flow Optimum And flow Roads in the Inter intersection Pretty Good. Data Collection Survey Do with How to Jump On The entire intersection. The Data That Is Taken Volume Vehicle Yang through Each intersection, Time Signal, Mileage Vehicle Speed ​​The Second through Geometric intersection and intersection. Acquired Data Is Used as Reference in New Planning Cycle Time with Noting Coordination Theory intersection. Best Performance At each intersection Then Coordinated Based on Total Flow Vehicle That Has Such Obtained from Survey Results. Settings Guide on Second Intersection with The Flow Limit Sign intothat intersection Inter Segment with Green Shortening Time of Lights Traffic Management to Toll Roads towards Inter intersection When Flow Distribution beyond the Allowed and Prioritize Major Flows from One Street intersection examined.   Keywords: Flow, Flow saturated, green signal, the cycle time.